2020
DOI: 10.3390/ijerph17113812
|View full text |Cite
|
Sign up to set email alerts
|

Association between Ambient Air Pollution and Hospital Length of Stay among Children with Asthma in South Texas

Abstract: Although hospital length of stay (LOS) has been identified as a proxy measure of healthcare expenditures in the United States, there are limited studies investigating the potentially important association between outdoor air pollution and LOS for pediatric asthma. This study aims to examine the effect of ambient air pollution on LOS among children with asthma in South Texas. It included retrospective data on 711 children aged 5–18 years old admitted for asthma to a pediatric tertiary care hospital in South Tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 43 publications
(59 reference statements)
0
13
0
Order By: Relevance
“…Many studies have demonstrated so far a clear association between short-term exposure to outdoor air pollutants and different asthma outcomes including asthma control [ 87 ], lung function [ 92 ], consumption of asthma medications [ 93 , 94 ], outpatient visits [ 95 , 96 ], asthma exacerbations [ 97 , 98 ], emergency room visits [ 99 ], hospitalizations [ 100 , 101 ], length of stay in the hospital [ 102 ] and deaths [ 2 ]. Several air pollutants have been implicated in the loss of asthma control.…”
Section: Outdoor Air Pollutionmentioning
confidence: 99%
“…Many studies have demonstrated so far a clear association between short-term exposure to outdoor air pollutants and different asthma outcomes including asthma control [ 87 ], lung function [ 92 ], consumption of asthma medications [ 93 , 94 ], outpatient visits [ 95 , 96 ], asthma exacerbations [ 97 , 98 ], emergency room visits [ 99 ], hospitalizations [ 100 , 101 ], length of stay in the hospital [ 102 ] and deaths [ 2 ]. Several air pollutants have been implicated in the loss of asthma control.…”
Section: Outdoor Air Pollutionmentioning
confidence: 99%
“…However, there was insufficient evidence to draw a similar conclusion regarding adult asthma [65]. Many studies have described correlations between short-term exposure to outdoor air pollutants and various aspects of asthma, including symptom control [66], lung function [67], medication dose [68,69], outpatient visits [70,71], asthma exacerbations [72,73], emergency room visits [74], hospitalizations [75,76], length of hospital stay [77], and mortality rate [78] (Figure 1). COPD is a disease characterized by exhaustion that frequently affects smokers and involves progressive respiratory symptoms, such as dyspnea and cough with sputum.…”
Section: The Effects Of Air Pollutants On Asthma and Copd Upper Airway Diseasementioning
confidence: 99%
“…Previous studies showed that PM 2.5 has a higher in uence on hospital admission than other air pollutants (Buczyńska et al 2014). PM 2.5 was positively associated with LOS among children (Baek et al 2020a). There was a short-term increase in hospital admission rates associated with PM 2.5 for all of the health outcomes except injuries (Dominici et al 2006).…”
Section: Discussionmentioning
confidence: 89%